2023
DOI: 10.1021/jacsau.2c00614
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Uranium Extraction Performance of Multivariate Covalent Organic Frameworks through Donor–Acceptor Linkers and Amidoxime Nanotraps

Abstract: Covalent organic frameworks (COFs) can be designed to allow uranium extraction from seawater by incorporating photocatalytic linkers. However, often sacrificial reagents are required for separating photogenerated charges which limits their practical applications. Herein, we present a COF-based adsorption-photocatalysis strategy for selective removal of uranyl from seawater in the absence of sacrificial reagents. A series of ternary and quaternary COFs were synthesized containing the electron-rich linker 2,4,6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 75 publications
0
42
0
Order By: Relevance
“…Discovering sustainable ways of harvesting uranium from seawater is critical to ensuring a reliable supply of uranium fuel for future generations (as well as being of importance in the treatment of wastewater from the nuclear industry and contaminated groundwater). COF-based adsorbent-photocatalyst systems are now being pursued for uranium extraction 46 48 . To date, the developed systems have relatively low activity for U(VI) reduction and/or need sacrificial reagents for separating photo-generated charges.…”
Section: Introductionmentioning
confidence: 99%
“…Discovering sustainable ways of harvesting uranium from seawater is critical to ensuring a reliable supply of uranium fuel for future generations (as well as being of importance in the treatment of wastewater from the nuclear industry and contaminated groundwater). COF-based adsorbent-photocatalyst systems are now being pursued for uranium extraction 46 48 . To date, the developed systems have relatively low activity for U(VI) reduction and/or need sacrificial reagents for separating photo-generated charges.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that copper ions cause a sequence of events that eventually lead to cell death. 55–58 The antibacterial mechanism of the CHM and CMM here could also be attributed to the release of Cu 2+ ions, which initially adsorb on the cell membrane of bacteria and then infiltrate into the cells through interactions with the hydroxyl groups of peptidoglycans, causing damage to the cell membranes and DNA breakage. The SEM images were further used to observe visually the morphological changes of E. coli and S. aureus after antibacterial experiments for CMM-70 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that once the formation of PAN can be widely avoided, using other monomers for copolymerization is also feasible. From the perspective of experiments and theoretical calculation, recent reports suggested that the adsorption strength of amidoxime for uranium is almost the highest. , Furthermore, the adsorption capacity of A-1 for uranium was 9.1 times higher than that of vanadium, while that of A-3 was 14.8 times. This may be due to the long distance between amidoxime groups on A-1 and the less modification amount of amidoxime.…”
Section: Resultsmentioning
confidence: 99%